11 Haemostatic radiotherapy in gastro-oesophageal cancer: referral patterns and treatment efficacy. (5th April 2017) - Walls, G; Turkington, R; Harrison, C
Abstract : Background: Haemorrhage from unresectable gastric and oesophageal malignancies reduces quality of life, shortens survival, and is associated with considerable burden for blood banks. Aim: The purpose of this study was to evaluate the outcomes of radiotherapy (RT) in achieving haemostasis, and to describe referral patterns to the Clinical Oncology team. Method: Retrospective analysis of all patients with gastro-oesophageal cancer that received RT with haemostatic intention from 2013–2016 in Northern Ireland. Only patients who required packed red cell transfusions were included. Study endpoints included improvement in haemoglobin (Hb) and transfusion requirement. Results: Haemostatic RT was used in 25 cases (13 oesophagus; 12 stomach). Mean age of patients was 77 years (44–89). Mean Hb nadir in the period from first Hb drop to RT was 64 g/L (36–99). Endoscopic intervention was performed in 3 cases (1 Haemospray and clip; 2 Haemospray only). Mean time from diagnosis to first evidence of haemorrhage was 4.5 months (0-12). Mean time from first Hb decrease to radiotherapy referral was 13 weeks (1–45). There was a statistically significant increase in the mean Hb following radiotherapy (87 g/dl to 103 g/dl; p<0.0001). Mean units of packed red cells transfused two months before versus after radiotherapy was 8.5 V 1.2. Mean overall survival after RT was 107 days with a trend to increased survival with increasing RT dose. Treatment failure (death or requirement for transfusion within one month of RT) was 9/24 (37%). Conclusions: Radiotherapy is an effective treatment for haemorrhage associated with gastro-oesophageal malignancy and referrals to Clinical Oncology should be considered early.